SMART method utilization for meetinghouse elections in Pekanbaru City - M. Khairul Anam; Purwanto; Agustin; Aniq Noviciatie Ulfah (STMIK Amik Riau, 2020)
Choosing and looking for information about the meetinghouse in Kota Pekanbaru is a problem for people in need. A Distance of distant location and limited information obtained. This application is built based on Android using Simple Multi-Attribute Rating Technique (SMART) method, there are several criteria used are rental price, capacity, and facilities. The application is built using the JAVA programming language with Android Studio. This system design analysis uses the Unified Modeling Language (UML). The results that this application can help users to choose existing meetinghouses in Pekanbaru City using the SMART method. The search result is a list of meetinghouse names in which there are various information about the meetinghouse and the location to the meetinghouse. The test results of the built-in application can work well and can address the problems faced by the user in determining the multipurpose building elections.